2020
DOI: 10.1542/peds.2019-3684
|View full text |Cite
|
Sign up to set email alerts
|

International Practice Patterns of Antibiotic Therapy and Laboratory Testing in Bronchiolitis

Abstract: BACKGROUND AND OBJECTIVES: International patterns of antibiotic use and laboratory testing in bronchiolitis in emergency departments are unknown. Our objective is to evaluate variation in the use of antibiotics and nonindicated tests in infants with bronchiolitis in 38 emergency departments in Pediatric Emergency Research Networks in Canada, the United States, Australia and New Zealand, the United Kingdom and Ireland, and Spain and Portugal. We hypothesized there would be significant variation, adjusted for pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 61 publications
1
25
1
1
Order By: Relevance
“… 28–30 Our results showed a very low use of antibiotics, consistently below 5%, compared with other countries, where rates in the range of 3.5%–11.1% are reported. 28 …”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“… 28–30 Our results showed a very low use of antibiotics, consistently below 5%, compared with other countries, where rates in the range of 3.5%–11.1% are reported. 28 …”
Section: Discussioncontrasting
confidence: 39%
“…24 25 Antibiotic treatment is not recommended for acute bronchiolitis, 9 26 27 and overuse is a known problem. [28][29][30] Our results showed a very low use of antibiotics, consistently below 5%, compared with other countries, where rates in the range of 3.5%-11.1% are reported. 28 We found a steady rise in the use of highflow oxygen in the hospital setting.…”
Section: Open Accesssupporting
confidence: 41%
“…Schuh et al 6 demonstrated in a prospective cohort that routinely obtaining a radiograph led clinicians to make pneumonia diagnoses that radiology review did not support and to prescribe antibiotics that did not appear to benefit patients. Zipursky et al, 3 in their multicenter study, similarly find that radiograph use was associated with antibiotic prescription, and the network in the United Kingdom and Ireland had the lowest rates for both laboratory testing and antibiotic use. Assignment of diagnosis codes may also vary because of different definitions of the condition.…”
mentioning
confidence: 91%
“…2 Specific recommendations vary, but research consistently shows that many of these interventions are unnecessary and may cause unwarranted cost and the potential for harm because of associated radiation, antibiotic exposure, and other effects. In this issue of Pediatrics, Zipursky et al 3 analyze testing protocols at a higher level by comparing trends across countries using a retrospective data set from the Pediatric Emergency Research Network (PERN), which combines 6 multicenter networks including 38 emergency departments from 8 countries in North America, Europe, the United Kingdom, Australia, and New Zealand. Authors of previous analyses addressed respiratory treatments 4 and prediction of severe disease, 5 but in this study, the investigators focus on antibiotics and laboratory testing.…”
mentioning
confidence: 99%
See 1 more Smart Citation